2020
DOI: 10.1089/ten.teb.2019.0316
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide in Dental Pulp Tissue: From Molecular Understanding to Clinical Application in Regenerative Endodontic Procedures

Abstract: Nitric oxide (NO), which is synthesized by the enzyme NO synthase (NOS), is a versatile endogenous molecule with multiple biological effects on many tissues and organs. In dental pulp tissue, NO has been found to play multifaceted roles in regulating physiological activities, inflammation processes, and tissue repair events, such as cell proliferation, neuronal degeneration, angiogenesis, and odontoblastic differentiation. However, there is a deficiency of detailed discussion on the NO-mediated interactions be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 199 publications
0
2
1
Order By: Relevance
“…The NO present in saliva is part of a nonspecific defense mechanism against periodontopathogenic bacteria [13] and plays a stimulatory role [14]. However, the chemical mechanisms of NO are complex processes involving numerous possible reactions with direct and indirect effects depending on different concentrations [15]. Surprisingly, in the present study, low and variable levels of NO were found to be not correlated with mucositis and pain.…”
Section: Discussioncontrasting
confidence: 76%
“…The NO present in saliva is part of a nonspecific defense mechanism against periodontopathogenic bacteria [13] and plays a stimulatory role [14]. However, the chemical mechanisms of NO are complex processes involving numerous possible reactions with direct and indirect effects depending on different concentrations [15]. Surprisingly, in the present study, low and variable levels of NO were found to be not correlated with mucositis and pain.…”
Section: Discussioncontrasting
confidence: 76%
“…Selected metabolic mediators inhibiting pulp inflammatory processes are presented in Table 2, together with their mechanisms of action. In addition, the interesting metabolite is nitric oxide, which not only regulates the physiological activities of the dental pulp cells but also can initiate and mediate the immune and inflammatory responses triggered by external stimuli [163]. It may play a crucial role in the interactions between inflammatory and regenerative processes in the dental pulp.…”
Section: The Anti-inflammatory Mechanisms Of the Potential Metabolic ...mentioning
confidence: 99%
“…Based on its critical role in DPSCs, the modulation of iNOS has been proposed as a valuable strategy to prevent the irreversible damage to the dental pulp tissue and to promote the regeneration of dentin-pulp complex [ 11 , 12 ]. However, only few studies have been published to date, which mainly investigated the effects of unselective, or toxic, iNOS inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…However, only few studies have been published to date, which mainly investigated the effects of unselective, or toxic, iNOS inhibitors. Moreover, inside the dental pulp tissue, endogenous NO is generated mainly by immunocompetent cells and dental pulp cells, and mediates not only inflammatory/immune activities, but also signaling cascades that regulate tissue repair and reconstruction, indicating its involvement in both tissue destruction and regeneration [ 11 ]. Basically, controlled, low levels of NO derived from the constitutive NOSs, mainly the eNOS, are essential under dental pulp physiological conditions, given the role played by NO in angiogenesis, tissue regeneration and perfusion [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%